Pengaruh Strategi Keunggulan Bersaing, Sumber Daya Perusahaan dan Implementasi Strategi Jenerik Terhadap Kinerja Usaha dengan Lingkungan Operasi Sebagai Variabel Moderating - Y. Djoko Suseno (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The objective of this research is to measure the influence of competitive advantage strategy resources and to the implementation of generic strategy towards furniture small-scale business in Central Java. In details, the objectives f the research are to analyze ad examine (1) the influence of competitive advantage strategy towards the implementation of small-scale generic strategy,(2) the influence of business environment certainty towards competitive advantage strategy and strategy and strategic resources,(3) the influence of competitive advantage strategy towards the performance of small-scale business (4)the influence of business environment certainty towards the implementation of generic strategy of small-scale business,(6) the influence of strategic resource towards the small-scale performance,(7)the influence of strategy implementation towards small-scale business performance. The samples were the 108 small-scale business taken using cluster system from the 248 small-scale business in seven Regency Central Java. The data collecting technique used were structured interview based on the questionnaire and observation. To test the pertern of the cause/effect relationship model having been formed, the researcher used analysis instrument capable of esplaining simultaneousely the Structural (AMOS) Program of 5.00 version. The research result shows that(1) the competitive advantage insignificantly gives positif influence towards the implementation og generic strategy,(2) business environment certainty significantly gives influence towards competitive advantage strategy and strategic generic ,(3) competitive advantage strategy significantly gives positive influence towards business performance,(4) business environment certainty significantly give influence towards business performance,(5) strategic resources significantly give positive influence towards the implementation of generic strategy,(6) strategic resource significantly give positive influence towards business performance, (7) the implementation of generic strategy significantly gives influence towards business performance.Keywords: Competitive advantage strategy business environment , strategic resources, the implementation of generic strategy and business performance.